Evangelii Gaudium: a retomada de tesouros escondidos do Vaticano II no magistério do Papa Francisco - Marcolino, Reginaldo (2024)
The present research seeks to reread the Apostolic Exhortation Evangelii Gaudium, a programmatic document of Pope Francis. Through Evangelii Gaudium, efforts will be made to rescue the “hidden treasures” of the Second Vatican Ecumenical Council in the current pontificate. For this purpose, an attempt will be made to expose, in general terms, the ecclesiological treaty from its beginnings, culminating in the revisitation of the Second Vatican Ecumenical Council. The post-Vatican II Latin American Episcopal Conferences, in particular the V Conference in Aparecida, will be objects of exposition and theological-pastoral analysis in the pontificate of Francis. Finally, among the various approach perspectives to rescue these “hidden treasures”, the current key issue will be worked on: synodality